Transcatheter aortic valve-in-ring implantation: feasibility in an acute, preclinical, pilot trial. (16th January 2019) - Andreas, Martin; Russo, Marco; Kuwata, Shingo; Cesarovic, Nikola; Wang, Changtian; Guidotti, Andrea; Lipiski, Miriam; Rankin, J Scott; Regar, Evelyn; Taramasso, Maurizio; Maisano, Francesco; Weber, Alberto
Abstract: OBJECTIVES: The HAART ring device has been introduced as a novel strategy to facilitate aortic valve repair. This rigid, elliptical device aims to restore normal leaflet configuration and to provide annular stabilization in the setting of aortic regurgitation. The goal of this preclinical study is to evaluate the in vivo feasibility of 'aortic valve-in-ring' transcatheter aortic valve replacement (TAVR). METHODS: Six animals landrace pigs, 87.6 [standard deviation (SD) 4.5] kg underwent HAART ring implantation (5 cases #19 mm and 1 case #21 mm) via full sternotomy with cardiopulmonary bypass. Seven transfemoral TAVR implantations were performed with the Medtronic EvolutR prosthesis to assess the sizing and outcome (5 cases #23 mm, 1 case #26 mm and 1 case #29 mm). RESULTS: TAVR implantation was successful in 6 of 7 attempts. Post-dilatation was performed in 1 case without damage of the ring or the valve. One embolization occurred due to oversizing (EvolutR valve 29 mm in HAART ring 19 mm). No clinically relevant postimplantation gradient [7.6 (SD 4.0) mmHg] or regurgitation was detected by invasive and echocardiographic measurements. Postoperative computed tomography scans revealed good device configuration. CONCLUSIONS: Transcatheter aortic valve-in-ring implantation of a self-expandable TAVR into a rigid aortic annuloplasty ring after aortic valve repair appears feasible. Proper sizing and correct depth of implantation are crucial.